Laparoscopic conservative management of ureteral endometriosis: a survey of eighty patients submitted to ureterolysis - Migliaretti Giuseppe; Berchialla Paola; Delpiano Elena; Bonino Luca; Camanni Marco; Revelli Alberto; Deltetto Francesco (BMC, 2009)
Abstract Background this study aims to evaluate the effectiveness and safety of laparoscopic conservative management of ureteral endometriosis. Methods Eighty cases of histologically confirmed endometriosis affecting the ureter, 10 of which with bladder involvement were prospectively studied. In detail, patients were 13 women with ureteral stenosis (7 with hydronephrosis), 32 with circular lesions totally encasing the ureter, and 35 with endometriotic foci on the ureteral wall, but not completely encasing it. They were submitted to laparoscopic ureterolysis with or without partial cystectomy, ureteroneocistostomy. The rate of surgical complications, the recurrence rate, the patients' satisfaction rate was assessed during 22 months (median) follow-up. Results Laparoscopic ureterolysis was employed for all patients and set free the ureter from the disease in 95% of cases, whereas ureteroneocystostomy was necessary for 4 patients showing severe stenosis with hydronephrosis, among which 2 had intrinsic endometriosis of the ureteral muscularis. Three post-surgery ureteral fistulae occurred in cases with ureteral involvement longer than 4 cm: two cases were successfully treated placing double J catheter, the third needed ureteroneocistostomy. During follow-up, ureteral endometriosis recurred in 2 patients who consequently underwent ureteroneocystostomy. Most patients expressed high satisfaction rate throughout the whole follow-up period. Conclusion laparoscopic ureterolysis is effective and well tolerated in most cases of ureteral endometriosis. Ureteroneocystostomy is a better strategy for patients with extended (more than 4 cm) ureteral involvement or with severe stenosis with or without hydronephrosis.